Analisis Kekuatan dan Kelemahan Kegiatan Dakwah Forum Komunikasi Islam Rabbani Universitas Andalas Padang - Yummil Hasan, Muhammad Jufri (FDIK IAIN Padangsidimpuan, 2019)
SWOT analysis of the FKI Rabbani missionary activities of AndalasUniversity (UNAND) Padang City was applied in every missionary activity carriedout in the UNAND campus environment. Can be seen on internal factors andexternal factors. From the internal factors of the FKI Rabbani University ofAndalas University (UNAND), the city of Padang which consists of two points,namely strengths and weaknesses, that the strength of the FKI Rabbani Universityof Andalas University (UNAND) in the city of Padang lies in financial resourcesoriginating from the Rector, the Alumni Council contribution, and donationscaretaker. Human resources, administrators are given guidance and ongoingtraining, so they are able to manage the course of campus missionary activities.Technology resources, administrators broadcast propaganda through social media,such as Facebook, Instagram. And information resources, from the Islamic StudyForum (FSI) Faculty of Andalas University (UNAND). While in terms ofweakness, it can be seen from the facilities and infrastructure, namely infocus. Lowmanagerial skills, such as the lack of communication among fellow management.Skills that are not in accordance with market demands, such as the need forpreaching to students is to use infocations and lecture materials. Products that areless desirable, such as the implementation of closed room activities.Keywords: Analysis, SWOT, Da'wahAbstrakAnalisis SWOT kegiatan dakwah FKI Rabbani Universitas Andalas(UNAND) Kota Padang diterapkan dalam setiap kegiatan dakwah yang dilakukandi lingkungan kampus UNAND. Dapat dilihat pada faktor internal dan faktoreksternal. Dari faktor internal FKI Rabbani Universitas Andalas (UNAND) kotaPadang yang terdiri dari dua poin yaitu kekuatan dan kelemahan, bahwa kekuatanFKI Rabbani Universitas Andalas (UNAND) kota Padang terletak pada sumberdaya keuangan yang berasal dari pihak Rektorat, sumbangan Dewan Alumni, sertasumbangan pengurus. Sumber daya manusia, pengurus diberikan pembinaan danpelatihan-pelatihan yang berkelanjutan, sehingga mampu mengelola jalannyakegiatan dakwah kampus. Sumber daya teknologi, pengurus menyiarkan dakwahmelalui media sosial, seperti facebook, instagram. Dan sumber daya informasi, dariForum Studi Islam (FSI) Fakultas selingkup Universitas Andalas (UNAND).Sedangkan dari segi kelemahan terlihat dari sarana dan prasarana, yaitu infokus.Kemampuan manajerial yang rendah, seperti masih kurangnya komunikasi sesamapengurus. Keterampilan yang tidak sesuai dengan tuntutan pasar, seperti kebutuhandakwah kepada mahasiswa adalah menggunakan media infokus dan bahan matericeramah. Produk yang kurang diminati, seperti pelaksanaan kegiatan diruangantertutup.Kata Kunci: Analisis, SWOT, Dakwah